Predictors of Attrition Among Accelerated and Traditional Physician Assistant Students. Issue 4 (December 2020) - Wolf, Corri; Ahmed, Anoma Zehra; Schmidt, Gordon; Winter, Sara
Abstract : Purpose: Students can be admitted to a physician assistant program via an accelerated bachelor of science/master of science (BS/MS) track or by a postbaccalaureate track. The purpose of this study was to identify predictors of student attrition based on differences in modes of admission. Methods: Student admissions and retention data were collected for 277 students in the physician assistant program at the New York Institute of Technology from the graduation years 2016 to 2020. A t -test was used to analyze differences among admissions methods for the following variables: age, cumulative grade point average (GPA), science GPA, and patient contact hours. Results: A total of 10.4% (n = 29) of students from the total enrollment left the program for academic reasons. These students had a significantly lower cumulative GPA (3.54 vs. 3.71) and science GPA (3.45 vs. 3.68), and fewer patient contact hours (951 vs. 1720) at admission ( p < .05). Furthermore, 44 students entered via the BS/MS track, and 41% (n = 18) were dismissed for academic reasons. This group of 18 BS/MS students comprised 62% of all students dismissed for academic reasons over the past 5 years. When considering only BS/MS students, those who left for academic reasons had a significantly lower science GPA (3.37 vs. 3.62, p < .05) than those who successfully completed the program. Conclusions: Having dual tracks of entry resulted in varying degrees of academic preparation and, for our institution, a disproportionate number of students from the accelerated track being dismissed despite meeting published admissions criteria.